Acute Toxicity and Hypoglycemic Effect of a Polyherbal Formulation on Blood Glucose in Oral Glucose Tolerance Test (OGTT) and Alloxan-Induced Diabetic Rats - Abednego Okeoghene Warri; Emuesiri Goodies Moke; Aishat Oyinkansola Balogun; Kennedy Chibogu Nzeh; Emuesiri Kohworho Umukoro; Earnest Oghenesuvwe Erhirhie (Biology, Medicine, & Natural Product Chemistry, 2021)
Madam F. Kayes Bitters® is an herbal formulation commonly used in Nigeria and some African countries in the management of diabetes mellitus and other diseases conditions. This study evaluated the in-vivo hypoglycaemic activity, as well as acute toxicity of the polyherbal formulation to provide its efficacy and safety. Healthy albino mice (20-30 g) and Sprague Dawley female rats (90-130 g) were used for this study. Acute toxicity study (LD50) of the herbal formulation was determined by methods originally described by Miller and Tainter in 1994. Following oral dosing with glucose (2 g/kg) in normal fasted animals, herbal formulation (HF) at various doses was administered and blood glucose levels at 30 minutes, 60 minutes, 90 minutes, and 120 minutes were taken and recorded. Diabetes was induced using alloxan 150 mg/kg and diabetic rats were given the HF at doses of 50, 100, and 200 mg/kg with glibenclamide 2.5 mg/kg used as standard drug treatment. Blood glucose level was determined on 1st day, 7th day, 14th and 21st day. The LD50 was greater than 5g/kg with oral administration. The oral glucose tolerance test showed that the group that received 100 mg/kg HF showed a significant reduction (p<0.05) in glucose level after 120 minutes when compared to the basal level of glucose recorded. All treated diabetic groups showed a significant decrease in glucose level on the 21st day. The herbal formulation of Hydrastis canadesis Aloe capensis, Echinacea angustifolia and honey exhibited a significant glucose-lowering activity in alloxan-induced diabetic rats.